Supply chain intelligence in business organizations: a Malaysian perspective - Jaharuddin, Nor Siah; Mohamed, Zainal Abidin; Sambasivan, Murali (Universiti Putra Malaysia Press, 2015)
The business environment has become more competitive due to advancements in technology and globalisation. Emphasising intelligence as a means for dealing with such circumstances, this study examined the role of supply chain intelligence (SCI), which embraces the process of competitive intelligence (CI) in the operations of a supply chain management (SCM). The integration is needed to ensure that this actionable information from CI has a 360-degree view of business activities amongst supply chains. What exactly is supply chain intelligence? How does supply chain intelligence influence business competitiveness in Malaysia? How does supply chain intelligence help businesses to achieve competitive advantages? This paper examined the contribution of supply chain intelligence on business competitiveness by: a) identifying and validating the dimension of supply chain intelligence components, and b) examining the levels of supply chain intelligence usage by businesses. A focus group was employed as a preliminary study to validate the supply chain intelligence components, and subsequently, for the development of the questionnaire for the survey in the study. The results contribute to the literature by emphasising the use of systematic intelligence in supply chain integration to improve business competitiveness.